Evaluation of different best management practices for erosion control on machine operating trails - Solgi, Ahmad (Array, 2019)
Ground-based mechanized forest operations often lead to increased runoff and soil loss on unbound forest roads and machine operating trails, which in turn can impede the technical trafficability of machines and cause negative impacts on the environment. The aim of this study was to evaluate the effectiveness of three Best Management Practice (BMP) treatments used to control erosion occurring on machine operating trails. The treatments included water bar, water bar and hardwood brush (H-brush), and water bar and softwood brush (S-brush). For a more comprehensive assessment of both brush treatments, two levels of brush thickness were tested; 0.5 m and 1.0 m. Results indicate that the most effective BMP treatments were the water bar and softwood brush followed by the water bar and hardwood brush and finally the least effective was the water bar. The average runoff rates and soil loss from the machine operating trails with the water bar treatment (52.64 l per plot, 8.49 g m-2) were higher than runoff and soil loss at the trails protected with hardwood brush (23.75 l per plot, 4.5 g m-2), and the trails protected by the hardwood brush had higher runoff and soil loss compared to trails covered by softwood brush (15.83 l per plot, 2.98 g m-2). Furthermore, results of this study showed that regardless of the treatment, the amount of runoff and soil loss decreased consistently as the thickness of the brush mat increased. Overall, erosion control techniques similar to either H-brush or S-brush that provide direct soil coverage should be used for erosion control, and final selection should be based on costs, availability of material, or landowner objectives.